PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN MENGGUNAKAN ANALISIS BENEISH M-SCORE PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2018 - Rifka Ayu Annisa; Imam Ghozali (Diponegoro Journal of Accounting, 2020)
This study aims to examine the detection of financial statement fraud using Beneish M-Score analysis. The dependent variable used in this study is Beneish M-Score. While, Days Sales in Receivable Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), Depreciation Index (DEPI), Selling, General and Administrative Index (SGAI), Total Accruals to Total Assets (TATA), and Leverage Index (LVGI) are used as independent variables. The data used in this study is secondary data. The sample of this study was taken using a purposive sampling method with a sample of 206 companies listed on Indonesia Stock Exchange in 2017-2018 and classified as manipulator based on the Beneish M-Score calculation. The analysis technique used to test the hypotheses is multiple linear regression analysis. Empirical results of the study showed that as many as 222 companies or 46.6% the sample were classified as manipulators, while 254 or 53.4% of the other companies were classified as non-manipulators. The study also found that DSRI, GMI, AQI, SGI, DEPI, and TATA had a positive and significant effect and that LVGI had a negative and significant effect on the Beneish M-Score. Meanwhile, SGAI did not have significant effect on Beneish M-Score.